Nilai-Nilai Akhlak dalam Kitab Syi’ir Ngudi Susilo Karya K.H. Bisri Musthofa - Kholid Mawardi; Rhenita Oktafiani; Hendri Purbo Waseso (Lembaga Penelitian, Penerbitan dan Pengabdian Masyarakat Institut Agama Islam Syarifuddin Lumajang, 2020)
This article reveals the contents of moral values ​​in the Book of Syi'ir Ngudi Susilo by K. H. Bisri Musthofa and their relevance to Islamic education. This research is included in the type of library research (library research) by discussing qualitative, while in collecting data using the library method, the analysis used in this thesis is content analysis (content analysis). The results obtained from this study are: (1) the collection of the Ngudi Susilo Syi'ir Book will mean from moral values, consisting of 9 (Nine) chapters that discuss morality in everyday life (2) moral values ​​that contained in this book are morals towards Allah, morals towards oneself, morals with parents, morals with educators, morals with nation and state, and morals with the environment. (3) the relevance of moral values ​​to Islamic education is the importance of involving and applying moral values ​​to the education of children from an early age. Education with Syi'ir can facilitate the internalization of moral values ​​in students.